2021
DOI: 10.2166/wcc.2021.238
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological impacts of climate and land-use change on flow regime variations in upper Indus basin

Abstract: Investigating the effects of climate and land-use changes on surface runoff is critical for water resources management. The majority of studies focused on projected climate change effects on surface runoff, while neglecting future land-use change. Therefore, the main aim of this article is to discriminate the impacts of projected climate and land-use changes on surface runoff using the Soil and Water Assessment Tool (SWAT) through the lens of the Upper Indus Basin, Pakistan. Future scenarios of the land-use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
3

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“… 45 , 46 The ensemble projections from multiple hydrological models can reduce parametric uncertainty in the hydroclimatic projections. 29 , 47 Other factors like land use/land cover change and construction of new reservoirs upstream of the existing hydropower dams can also impact river flow regimes and sediment load to the reservoirs, 48 , 49 , 50 , 51 which can influence hydropower potential in the future. The projected increase in high-flow events can increase sedimentation in the reservoir, which can further reduce the storage capacity.…”
Section: Discussionmentioning
confidence: 99%
“… 45 , 46 The ensemble projections from multiple hydrological models can reduce parametric uncertainty in the hydroclimatic projections. 29 , 47 Other factors like land use/land cover change and construction of new reservoirs upstream of the existing hydropower dams can also impact river flow regimes and sediment load to the reservoirs, 48 , 49 , 50 , 51 which can influence hydropower potential in the future. The projected increase in high-flow events can increase sedimentation in the reservoir, which can further reduce the storage capacity.…”
Section: Discussionmentioning
confidence: 99%
“…For the present study, the linear scaling (additive and multiplicative) and delta change correction (additive and multiplicative) bias correction approaches were employed (Haleem et al, 2021).…”
Section: Bias Correction Of Gcmsmentioning
confidence: 99%
“…Furthermore, conceptual models for hydrology have demonstrated the propensity to underestimate higher flows, particularly in instances of flood occurrences subsequent to intense rainfall. Studies utilizing conceptual hydrological models have found underestimation of peak flows in numerous locations, such as in-the Pakistan (Haleem et al 2022;Masood et al 2023), Norway (Huang et al 2019), US (Shrestha et al 2019), and other areas (Molina-Navarro et al 2014;Bizuneh et al 2021;Valeh et al 2021).…”
Section: Introductionmentioning
confidence: 99%